Daily hassles and uplifts at work: affective and cognitive processes and outcomes on subjective well-being - Silva, Ana Luísa Junça da (2015)
This thesis focuses on the relationship between affective daily events and employee well-being, and includes eight empirical studies. Studies 1 and 2 aimed to validate three measures of well-being for the Portuguese population (the subjective happiness scale, the flourishing scale and the scale of positive and negative experiences). Results showed good psychometric and structural properties for the three scales. The aim of Study 3 was to contribute to the identification of affective daily events (daily hassles and uplifts) and the affective reactions’ features. Results allowed the aggregation of daily hassles and uplifts into categories and showed that different events trigger different types of affective reactions, regarding the level of activation, duration and perceived effects for the employee. Study 4 sought to obtain evidence concerning the relationship between affective daily events, cognitive appriasals and emotional activation. Results showed that the role of cognitive appraisals on the link between affective events and affect is different for daily hassles and uplifts. In particular, the cognitive appraisal of the event’s intrinsic pleasantness does not interact with the event’s importance to influence emotional activation when daily uplifts were analyzed. On the opposite, the interaction between daily hassles, and both cognitive appraisals of importance and intrinsic (un)pleasantness was significantly stronger to positively influence the emotional activation level. Based on study 3 and 4, we developed and validated a generic measure of affective daily events (study 5). A multi-sample approach allowed us to conclude that the measure was reliable and, thus can be used to study affective events at work. Plus, the measure showed significant correlations with positive and negative indicators of mental health and attitudes in the workplace. With Study 6, we aimed to test whether hassles and uplifts would interact to predict the risk of mobbing. Results showed that having support from the leader (uplifts) buffered the negative effects of hassles (role ambiguity) on the risk of mobbing. Study 7 aimed to analyse the role of daily hassles and uplifts on the link between optimism and employee well-being. Our results showed that daily hassles played a mediating role between optimims and employee well-being, and daily uplifts moderated this indirect effect. At last, Study 8 presented multi-sample diary studies to analyse whether employee well-being would present fluctuations across time. Results demonstrated that, not only well-being presented within-person variations across time, but also demonstrated that affective daily events accounted for such fluctuations. Moreover, results from multilevel analyses demonstrated that work engagement mediated the impact of affective daily events on employee well-being, in an immediate manner. Based on these empirical studies, this thesis also evidences other variables (e.g., optimism) that influence the relationship between what happens at work, and what, and how those occurences make employees feel. The results of this multisample, multi-method thesis supported most of the hypotheses. In conclusion, the eight empirical studies of this thesis contribute to the literature on affective events theory and subjective well-being. This thesis suggests ideas for future research and provides practical implications regarding work design, the development of positive environmental conditions at work, and human resource practices that are based on the empirical findings reported. One advantage of these empirical studies is that they capture the dynamic and temporal aspects of daily events and its consequences such as affective states, work engagement and subjective well-being.